Early detection of autism spectrum disorders: From retrospective home video studies to prospective 'high risk' sibling studies. (August 2015) - Costanzo, Valeria; Chericoni, Natasha; Amendola, Filomena Alessandra; Casula, Laura; Muratori, Filippo; Scattoni, Maria Luisa; Apicella, Fabio
Highlights: We present an exhaustive review of methods used to investigate early signs of ASD. We focused on the methodological changes that have characterized studies over years. Pros and cons of different methodological approaches are discussed. Abstract: In the autism spectrum disorders (ASD) field of research there is scientific consensus on the importance of early identification (and subsequently, of timely treatment) for a better prognosis. For this reason, early diagnosis represents a common challenge for clinicians and an area of great interest for researchers. In the past decades, many studies have focused on identifying subclinical signs of ASD with different types of experimental designs and methods, both retrospectively and prospectively. The purpose of this narrative review is to present changes in methodology, from a historical point of view, highlighting the strengths and weaknesses of different research designs. Conclusions are drawn taking into account potentialities of prospective designs for the study of early predictors of ASD.